CONTROL OF VIBRATIONAL POWER INPUT TO SEMI-INFINITE ANISOTROPIC BEAM - Abd Rahman, Roslan (Jurnal Mekanikal, 2018)
The time averaged vibration power input to semi-infinite beam of anisotropic materials subj ected to simultaneously acting bending f orce and moment excitations is presented. Fibre-reinforced composite materials of seve ral types ofply and ofvarious laminate arrangement were selected. The power input was minimized due to cancellation effect attributed to the coupling mobility between f orce and moment components. The cancellation effe ct f requency could be controlled by regulating the properties ofthe anisotropic materials.